Evaluating the unexplored recreational fishing in the Turkish Black Sea: socio-economic significance and environmental impact - Erbay, Murat; Carlson, Anna; Grati, Fabio (Frontiers in Marine Science, 2024)
Marine recreational fishing, a globally popular outdoor activity, has deep cultural roots and ecological implications. This study, conducted between 2021-2022, explores marine recreational fishing practices along the Turkish Black Sea coast. It analyzes fisher numbers and demographics, fishing effort, fishing methods, and species caught and released. Furthermore, the research sheds light on the economic dimensions, emphasizing the substantial contributions of recreational fishing to local economies. Notably, responsible practices, such as catch-and-release initiatives, demonstrate anglers’ awareness of conservation efforts. Within the Turkish Black Sea region, an observed 18.5% participation rate among a population of 24.5 million implies the presence of approximately 4.5 million marine recreational fishers. Annually, this translates to nearly 30 million fishing days, accompanied by a total expenditure of 400 million Euros. However, it’s imperative to handle these figures cautiously as the timing of the screening survey during the COVID-19 pandemic may have influenced the high participation rate, introducing a potential bias. A detailed examination of a Turkish marine recreational fisher engaged in Black Sea fishing reveals an average annual catch of 16.5 kg of retained fish and 1.2 kg of released fish biomass. When extrapolated to the larger population of 4.5 million fishers, this culminates in a noteworthy landing biomass approaching 74,000 tons. The study unveils that marine recreational fishers in the Turkish Black Sea predominantly target commercially important species, resulting in a retained biomass surpassing commercial landings in 2021. This prompts concerns about potential impacts on crucial commercial fish stocks, underscoring the imperative inclusion of recreational fisheries in stock assessments. The research, providing essential insights into the intricate dynamics of recreational fishing, lays a foundation for well-informed policies and practices that concurrently promote environmental conservation and the continuation of this valued leisure activity.